Does Landscape Complexity and Semi-Natural Habitat Structure Affect Diversity of Flower-Visiting Insects in Cucumber Fields? - Akhmad Rizali; Damayanti Buchori; Susilawati Susilawati; Pudjianto Pudjianto; Yann Clough (AGRIVITA, Journal of Agricultural Science, 2018)
Presence of insects in agricultural habitat is affected by the surrounding circumstances such as the complexity and structure of landscape. Landscape structure is often formed as a consequence of the fragmentation of semi-natural habitat, which can negatively affect species richness and abundance of insects. This study was aimed to study the effect of complexity and structure of landscape on the diversity, abundance and traits of flower-visiting insects in cucumber fields. This study was conducted in cucumber fields surrounded by other agricultural crops, shrubs, semi-natural habitat and housing area, in Bogor, Cianjur and Sukabumi regencies, West Java, Indonesia. In a total of 16 agricultural areas, complexity and parameter of landscape especially class area (CA), number of patches (NumP), mean patch size (MPS), total edge (TE), and mean shape index (MSI) of seminatural habitats were measured. Sampling of flower-visiting insects was conducted using scan sampling methods. The result showed that landscape complexity affected species richness (but not abundance and trait) of flower-visiting insects both for mobile and less-mobile insects. Flower-visiting insects also responded differently to landscape structure. Species richness, abundance and variation of body size of mobile insects were affected by structure of semi-natural habitat.